The dental remains from the Early Upper Paleolithic of Manot Cave, Israel. Issue 160 (November 2021) - Sarig, Rachel; Fornai, Cinzia; Pokhojaev, Ariel; May, Hila; Hans, Mark; Latimer, Bruce; Barzilai, Omry; Quam, Rolf; Weber, Gerhard W.
Abstract: This study presents the dental remains discovered at Manot Cave (MC), Western Galilee, Israel. The cave contains evidence for human occupation during the Early Upper Paleolithic period (46–33 ka) mainly of Early Ahmarian (∼46–42 ka) and Levantine Aurignacian (∼38–34 ka) cultural levels. Six teeth (three deciduous and three permanent) were found at the site, of which four could be thoroughly analyzed. The morphology of the teeth was qualitatively described and analyzed using traditional and geometric morphometric methods. A large comparative sample was used in order to assess the morphological affiliation of the Manot specimens with other Homo groups. The results provided equivocal signals: the upper first premolar (MC-9 P 3 ) is probably modern human; the upper deciduous second molar (MC-10 dm 2 ) and the upper second permanent molar (MC-8 M 2 ) might be modern humans; the lower second deciduous molar (MC-7 dm2 ) might be Neanderthal. Owing to the small sample size and the almost total lack of distinctive characteristics, our outcome could not supply conclusive evidence to address the question of whether Manot Aurignacian population came from Europe or descended from the local Ahmarian population.